Bio-based visual optical pressure-responsive sensor. (15th May 2021) - Sun, Chengyuan; Zhu, Dandan; Jia, Haiyan; Yang, Chongchong; Zheng, Zhen; Wang, Xinling
Graphical abstract: Highlights: A bio-based visual optical pressure-responsive sensor is prepared. External pressure can be quantified with linear correlation between pressure and transmittance of sensor's reflectance peak. The sensor shows sensitivity to a wide range of pressure by choosing its PAAM elastomer. The pressure-responsive iridescent structural colors are regulated by PEG content. The sensor exhibits outstanding fatigue resistance after multiple compression-recovery cycles. Abstract: A bio-based pressure-responsive sensor with adjustable structural color is prepared by combining aerogel skeleton of cellulose nanocrystals (CNCs)/poly(ethylene glycol) (PEG) obtained via the ice-templating method with flexible polyacrylamide (PAAM) elastomer. The white aerogel is composed of consecutive ribbons, demonstrating chiral nematic structure. These ribbons are rearranged to be vertical to the force direction, leading to immediate appearance of the structural color when the 3D aerogel transforms to a 2D plane. Helical pitches are regulated by the PEG content that the wavelength of structural color covers up to 178 nm. There is an excellent linear correlation between pressure and transmittance of reflectance peak, and the sensitivity to pressure can be regulated by changing solid content of PAAM. Furthermore, the pressure-responsive color is still vivid after 16 cycles of compression. This flexible material with pressure-responsive structural color is promising in sensing, intelligent display, information transmission, and etc .